Effect of Additional CO2 and N2 Gas Blanket On Biodiesel Psychochemical Properties in Storage Tank - Wahyudi, Dedy; Fawzi, Mas; Cahyono, Beny (International Journal of Integrated Engineering, 2022)
Abstract: Ship movement and contaminants may be the main causes of accelerated biodiesel degradation during the ship storage process. One of the techniques to protect biodiesel storage on the ship is by applying a blanketing system. In this study, CO2, N2, and natural air blankets were added to the biodiesel stainless steel tanks (B100 and B50) that swing in the sinusoidal to simulate ship movement at sea and It was stored for six months. The Physicochemical properties of biodiesel gas blanket were tested according to ASTM and EN standards. The result in this study was found that storing biodiesel in a blanket with natural air, CO2, and N2 gases for 210 days has changed the biodiesel properties in proportional to the storage duration. The addition of CO2 gas blanket was influenced to reduce the oxidation times, and water content. On another side, it has increased the value of particle count, TAN, flash point, Kinematic Viscosity, and density. While additional N2 gas blanket does not have an extreme effect on the biodiesel properties. Keywords: Biodiesel, Storage, Degradation, Characteristic, Gasses blanket